THE USE OF MESORHIZOBIUM CICERI 2 TO INCREASE THE EFFICIENCY OF THE SYMBIOTIC SYSTEM OF CHICKPEA PLANTS - Umarov , B.R.; Yadgarov , Kh.T.; Abzalov , M.F.; Sagdieva , M.G. (Eurasian Journal of Applied Biotechnology, 2015)
The interaction of nodule bacteria with leguminous plants exhibits specificity, which is a characteristic that indicates that a nodule will form only beside the determined host plant. The most of specificity typical of in process evolution promoted leguminous mode rate widths. A study of nodule bacteria and chickpea plants sprouting on the territory of the Institute of Genetics and Plant Experimental Biology in Uzbekistan revealed data for the plants that enter into symbiosis with Mesorhizobium bacteria. In sterile conditions that microvegetation experience in greenhouse conditions, the symbiosis of the Mesorhizobium ciceri 2 nodule bacteria and chickpea plants and the formation of nodules on the root of the plant were studied. А in vegetation experience in containers has 10 L are received more results entering in symbiosis of the plant with nodule bacteria and arbuscular mycorrhizal fungus. The shaping of the symbiosis of the plant in the field with the microorganism was examined. The experiments in the natural conditions showed that, with the M. ciceri 2 strain, the size of the seeds on the plants increased an average of 10%, but, with the arbuscular mycorrhizal fungus, seed productivity increased an average of 40%, and the gain of the mass of 1,000 seeds was 20%. The gain of the biomass of the plants increased an average of 25%. These results suggest that the inoculation of chickpea seeds with microbiological preparations shape the symbiotic device and increase their productivity.